Metode Pengajaran di Sekolah Dasar Islam Perspektif Ibnu Sahnun - Tabrani ZA; Syahrizal Syahrizal (2022)
This paper aims to discuss the thoughts of Ibn Sahnun's Islamic education, which was critically analyzed related to teaching methods in Islamic Elementary Schools. Islamic Elementary Schools are essentially schools that implement the concept of Islamic education based on the Qur'an and Sunnah. The operational idea of Islamic Elementary School is an accumulation of the process of civilizing, inheriting, and developing Islamic teachings, culture, and civilization from generation to generation. Ibn Sahnun's thoughts on education have been mentioned, among others, in his book Adab al-Mu'allimin. This book has become a maestro and reference for many scholars. It is considered the first book to discuss education separately from other branches of science, such as schools and philosophy. Ibn Sahnun's educational concept consists of two parts; The first is compulsory education, and the second is non-binding or voluntary education. Ibn Sahnun's thoughts in the education field were complete and programmed, especially for classical times, because only a few figures were engaged in the field of education at that time. We can find some things that are still relevant today from these concepts.